La panthère des monts Mandara, de l’effroi à l’oubli - Christian Seignobos (Revue d'ethnoécologie)
Since the early 1980’s, no leopard (Panthera pardus) had been spotted in the Mandara mountains. Leopards were fearsome felines, they represented leadership in the animal world and were a symbol of power for human leaders. Leopards have shaped the mentality of the mountaineers, from their daily behaviors to the development of their habitats; not to mention their predominance in the tales and fabliaux. Their disappearance gave way to “mystical” panthers, created by sorcerers, and their image is already beginning to fade in these very fabliaux.